2018
DOI: 10.3390/joitmc4030033
|View full text |Cite
|
Sign up to set email alerts
|

Framing Open Innovation in Start-Ups’ Incubators: A Complexity Theory Perspective

Abstract: Recently, concepts and principles from the Complexity Theory (or, generally speaking, the complexity sciences) have been applied as a perspective for capturing the influence of the context, interaction, and adaption in the innovation processes, such as the ones enabled in the business incubators. The purpose of this paper is to implement a frame of reference for understanding the start-ups' incubator as a complex system where innovation, learning, and self-organization take place. We build on the interfaces be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…This study mainly focused on research that indicated that participation and [60] noted that communication has a significant effect on organizational innovation, and a study by Chun (2006) [132] stated that public officials' participation is the most important factor in the techniques for achieving innovation in government organizations. Several other studies have also found that participation and communication have a positive effect on organizational innovation [16,34,36,[56][57][58][59][62][63][64][65][66][67]108,111,[133][134][135][136].…”
Section: Change Management and Organizational Innovationmentioning
confidence: 88%
See 1 more Smart Citation
“…This study mainly focused on research that indicated that participation and [60] noted that communication has a significant effect on organizational innovation, and a study by Chun (2006) [132] stated that public officials' participation is the most important factor in the techniques for achieving innovation in government organizations. Several other studies have also found that participation and communication have a positive effect on organizational innovation [16,34,36,[56][57][58][59][62][63][64][65][66][67]108,111,[133][134][135][136].…”
Section: Change Management and Organizational Innovationmentioning
confidence: 88%
“…Hussain et al (2013) [71] highlighted that organizational learning has a significant positive relationship with organizational innovation, thereby illustrating the significance of education and training for organizational innovation. Several other studies have also demonstrated the positive effect of education and training on organizational innovation [60,69,72,73,136,[137][138][139]].…”
Section: Change Management and Organizational Innovationmentioning
confidence: 99%
“…Small changes in individual adaptation strategies can lead to substantial changes throughout the system [61]. Depending on the business life cycle or market conditions, open innovation strategies can be taken or discarded [62,63]. The biotechnology industry is no exception.…”
Section: Discussionmentioning
confidence: 99%
“…Da combinação das práticas de inovação aberta e serviços prestados pelas incubadoras de startups, há o surgimento de um sistema complexo, com maneiras diferentes de habilitações (BATTISTELLA et al, 2018).…”
Section: Combinação De Práticas De Inovação Aberta E Incubadorasunclassified